Ultrasonic evaluation of metoclopramide’s effect on gastric motility in emergency trauma patients - Lin, Huan; He, Jing-Jing; Cai, Zhi-Shi; Lu, Zhi-Wei; Lin, Zhi-Jian; Lin, Xian-Zhong; Huang, Qiao-Wen (Frontiers in Physiology, 2023)
Objective: This study used bedside ultrasound to evaluate the effect of metoclopramide on gastric motility in patients with emergency trauma. Methods: Fifty patients underwent ultrasound immediately after attending the emergency department of our hospital due to trauma. The patients were divided randomly into a metoclopramide group (group M, n = 25) and a normal saline group (group S, n = 25). The cross-sectional area (CSA) of the gastric antrum was measured at 0, 30, 60, 90, and 120 minutes (T = time). The gastric emptying rate (GER), GER/min, gastric content properties, Perlas grades at different times, T120 gastric volume (GV), and GV per unit body weight (GV/W) were evaluated. The risk of vomiting, reflux/aspiration, and the type of anesthetic treatment were also evaluated. Results: The differences in the CSA of the gastric antrum and the GV at each time point between the two groups were statistically significant. The CSA of the gastric antrum and the GV in group M were lower than those in group S, and the largest differences between the two groups occurred at T30. The differences in the GER and GER/min at each time point between the two groups were statistically significant; those in group M were higher than in group S, and the largest differences between the two groups occurred at T30. There were no obvious change trends in the properties of the gastric contents and the Perlas grades in both groups, and the differences were not statistically significant. The differences in the GV and GV/W at T120 between the two groups were statistically significant. The difference in the risk of reflux and aspiration at T120 was statistically significant. Conclusion: When metoclopramide was used in satiated patients with emergency trauma, it accelerated gastric emptying in the first 30 minutes and reduced the risk of accidental reflux; however, the normal gastric emptying level was not achieved, which could be attributed to the delaying effect of trauma on gastric emptying.